Psychological Benefits of a Sport-Based Program for Female Cancer Survivors: The Role of Social Connections - Durosini, Ilaria; Triberti, Stefano; Sebri, Valeria; Giudice, Alice Viola; Guiddi, Paolo; Pravettoni, Gabriella (Frontiers in Psychology, 2021)
In the context of sports-based interventions for improving health and quality of life in chronic patients, participants could develop meaningful social relationships that affect their well-being as much as intervention activities. In this study, 80 female cancer survivors participated in a running-based group intervention (2 sessions/week; 1,5 h), while 51 acted as controls. The intervention lasted approximately 5 months. Unfortunately, the length of the intervention was reduced and sport activities were altered by the COVID-19 pandemic and lockdown mid-intervention, while the shared therapy sessions continued online. This possibly altered the results, as anxiety, depression and physical aspects did not show significant differences between the experimental and control groups after the intervention. Participants reported positive comments on the experience as a whole, especially regarding the positive influence of the newly developed social connections. This was corroborated by significant correlations between group perceived cohesion and anxiety, depression, self-efficacy, and positive experience with the group psychological support. Overall, it is possible to suggest that in the program an important role was played by social connections and support, peer influence and the group experience, preserving positive experiential qualities of the intervention even if it was altered by external circumstances.